2021
DOI: 10.3390/vaccines9080858
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy and Uptake among Nursing Staff during an Active Vaccine Rollout

Abstract: Even with the availability of COVID-19 vaccines, factors associated with vaccine hesitancy and uptake among nurses are unknown. This study evaluated COVID-19 vaccine hesitancy and uptake of nursing staff during one of the first COVID-19 vaccine rollouts in the United States. A cross-sectional survey was conducted during February 2021 among nursing staff working in a large medical center in central United States. There were 276 respondents; 81.9% of participants were willing to receive the vaccine during the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
4
24
1
Order By: Relevance
“…In our comprehensive survey of employees of a large safety net county health system conducted between March and April 2021 when COVID-19 vaccinations were being administered in the US, we found that 9.4% overall were hesitant and 5.3% refused to be vaccinated, which is consistent with studies that have estimated 8–18% hesitancy [ 3 , 42 ]. These proportions contrast markedly from general population estimates of 20–30% resistant or refusing vaccination [ 13 , 14 , 15 , 16 , 23 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our comprehensive survey of employees of a large safety net county health system conducted between March and April 2021 when COVID-19 vaccinations were being administered in the US, we found that 9.4% overall were hesitant and 5.3% refused to be vaccinated, which is consistent with studies that have estimated 8–18% hesitancy [ 3 , 42 ]. These proportions contrast markedly from general population estimates of 20–30% resistant or refusing vaccination [ 13 , 14 , 15 , 16 , 23 ].…”
Section: Discussionsupporting
confidence: 85%
“…We see an opportunity in educational programs, given that employees who were vaccine hesitant had less knowledge of COVID-19 disease, despite their employment within a health system. Among nursing staff surveyed in February 2021 at a large healthcare facility, self-reports of the adequacy of information to make an informed decision about vaccination were lower among a hesitant group compared with both a willing and unwilling to be vaccinated group [ 42 ]. Our data further suggest that messaging from colleagues or family members, within social media networks or by religious leaders is less likely to sway hesitant health system employees to be vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that 624 (48.7%) of the healthcare workers were vaccinated for COVID-19 at least once, while 37.4% of them were fully vaccinated. This was lower than coverages in developed countries such as the United States (83.3%) [23] and developing countries such as Ethiopia (62.1%) [24]. One of the major contributors to vaccine hesitancy in Somalia and indeed most countries has been misinformation driven by social media platforms that the COVID-19 vaccines tend to make one infertile [25,26].…”
Section: Discussionmentioning
confidence: 94%
“…33 But, it was lower than the study findings in other developed countries such as New York City (82%). 34 The reason might be due to the increased morbidity and mortality rates in those countries, variation in the study periods and also due to the late arrival of the vaccine in Ethiopia. This study was also supported by a study conducted in low-and middle-income countries (LMIC) which indicated that COVID-19 vaccine acceptance across LMIC ranged from 66.5% to 96.6% with an average of 80.3%.…”
Section: Discussionmentioning
confidence: 99%